تقنيات السرد في رواية فلسطين العاشقة والمعشوق لعبد الله غالب البرغوثي - بشيرة عناد; بسمة قسومة; بثينة بعاج; فاطمة الزهرة شريط; تسنيم شعباني (جامعة الوادي - University of Eloued, 2025)
الملخص: تهدف هذه الدراسة إلى تسليط الضوء على تجربة سردية مقاومة في رواية"فلسطين العاشقة والمعشوق" لعبدالله غالب البرغوثي، من خلال الكشف عن ابرز تقنيات السرد الموظفة فيها، ومدى نجاحها في خدمة البنية الروائية ونقل القضية الفلسطينية من منظور ادبي. تناولت الدراسة المفاهيم النظرية المرتبطة بالسرد، ثم انتقلت إلي الجانب التطبيقي بتحليل الشخصيات، الزمان والمكان، الحدث، والرؤية السردية، وصولا إلي ملامح السرد المقاوم في النص. وقد اعتمدت الدراسة عن المنهج التحليلي الوصفي، واستندت إلي مجموعة من المراجع النقدية الحديثة لتفسير الظواهر السردية. Abstract: This study aims to highlight the narrative experience of resistance in Abdullah Ghalib al-Barghouti's novel “Palestine, the Lover and the Beloved” by revealing the most prominent narrative techniques employed in it and the extent to which they succeed in serving the novel's structure and conveying the Palestinian cause from a literary perspective. The study addressed the theoretical concepts related to narrative, then moved on to the practical aspect by analyzing the characters, time and place, events, and narrative vision, leading to the features of resistance narrative in the text. The study adopted a descriptive analytical approach and drew on a range of modern critical references to interpret narrative phenomena.
مذكرة دراسات أدبية
Keywords: : تقنيات السرد، رواية فلسطين العاشقة والمعشوق لعبدلله غالب البرغوثي، السرد المقاوم، الشخصيات، الزمان، المكان، الحدث; Keywords: Narrative techniques; Abdullah Ghalib al-Barghouti's novel Palestine; the Lover and the Beloved; resistance narrative; characters; time; place; events..